Isolation, Characterization and Antianxiety Activity of Pentacosan-13-ol from Ferula sumbul Hook. Roots. Issue 3 (4th May 2018) - Batra, Sonali; Kumar, Ashwani; Sharma, Anupam
Abstract: Ferula sumbul Hook. (Apiaceae) has been traditionally used as a sedative in hysteria and other nervous disorders. Present study aims to isolate the antianxiety constituent(s) from F. sumbul roots using bioactivity guided fractionation approach. Dried coarsely powdered of F. sumbul roots were subjected to successive exhaustive Soxhlet extraction using petroleum ether, chloroform and ethanol. Finally, decoction of the marc was prepared using distilled water. The extracts were screened for antianxiety activity in mice using elevated plus maze model at three different dose levels. Chloroform extract, exhibiting significant antianxiety activity, was subjected to column chromatography to obtain 4 fractions (F1 -F4 ) which were further evaluated for antianxiety activity. Column chromatography of F4 yielded 5 sub-fractions (F4.1 -F4.5 ) and a white amorphous compound. All these were evaluated for antianxiety activity. Characterization studies elucidated the structure to be pentacosan-13-ol. The compound exhibited significant antianxiety activity at the dose of 20 mg/kg, po. Present study validates the traditional use of F. sumbul roots in nervous disorders. Pentacosan-13-ol is the antianxiety constituent of F. sumbul roots. This is the first report on antianxiety activity of F. sumbul roots.